RETRACTED: Magnetic resonance imaging and 18F-fludeoxyglucose positron emission tomography/computed tomography findings of retroperitoneal clear cell carcinoma with an unknown primary site: A case report - Zeng, Dao-Bing; Chang, Chan; Liu, Xu-Sheng; Gao, Yan; Wang, Ya-Lan; Pei, Zhi-Jun (Frontiers in Medicine, 2022)
A 46-year-old man presented with low-grade fever, hyperhidrosis, and fatigue at night for the past 20 days. His weight decreased significantly within 2 months (approximately 12 kg). On abdominal ultrasound, a mass near the left renal hilum was observed. In addition, enhanced magnetic resonance imaging (MRI) of the abdomen revealed a retroperitoneal nodular mass; however, no abnormalities in either kidney or adrenal glands were observed. 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) demonstrated an intensely FDG-avid retroperitoneal mass (SUVmax 19.6). On March 8, 2021, left retroperitoneal lesion resection, retroperitoneal lymph node dissection, and double kidney exploration were performed under general anesthesia. The postoperative pathological examination showed clear cell carcinoma (left retroperitoneal) and metastatic lymph nodes (Level I). The immunohistochemical results showed that the tumor originated from the kidney.There have been no previous reports on this subject in the literature. Herein, we report the case of clear cell carcinoma in the retroperitoneum confirmed by the pathology report. Although immunohistochemistry suggested renal origin, no obvious abnormality was found in imaging and exploration of both kidneys during operation.